Control interno contable y su aporte a la razonabilidad de las cuentas y documentos por cobrar - Quezada Zaruma, Edgar Patricio (2015)
The internal accounting control applied to the portfolio receivables of a company, is listed as the key component of the accounting and financial systems, operational information of the organization and process planning for errors or deficiencies that prevent the normal development of activities loan recovery and purification of bad, the company generating the financial resources necessary for the normal development of its operations. To make the diagnosis of the company, internal control to the heading of the accounts and notes receivable was implemented, resulting in inconsistencies in the recovery of the portfolio. The project is mainly based on the descriptive method using techniques such as observation, interviews and questionnaires to define the most important events within the company using the internal control. This research is based primarily on implementing policies to optimize collection recovery portfolio and generate cash in the company. The receivables portfolio is the category that integrates the active generator of future benefits for the organization; therefore its control must be rigorous to meet business objectives. The proposed policy generation collection and recovery portfolio streamlines the development process of income generation and detection of errors in the presentation of information and its reasonableness. In conclusion, the internal accounting control and its application according to the loan recovery policies Rosimarket commissary, is the need for established processes are applied optimal and timely component. As a recommendation the possibility of applying internal control and define the different processes and areas of the company arises, checking the accuracy of the information presented in the financial statements.